DETECTION AND ANALYSIS OF EARLY GENES OF WHITE SPOT SYNDROME VIRUS IN PENAEID SHRIMP - S, Dinesh.; M, Roohi Fatima.; Patil, Komal B; Verma, Kanika; Gupta, Noopur; Thenamkodath, Liz; Menon, Priyanka; T, Mekata.; T, Itami.; R, Sudhakaran. (Vietnam Journal of Marine Science and Technology, 2015)
White spot syndrome virus (WSSV) is the most lethal pathogenic virus affecting the penaeid shrimp. Outbreak of WSSV causes high mortality among the populations of cultured penaeid shrimp. Aim of the present study was to diagnose the WSSV in early stage of infection. Immediate early genes are genes that are activated due to presence of cellular stimuli and have significant role in replication and proliferation of virus. In this study, wsv303 and wsv477 genes were chosen for analysis. This study demonstrates the detection of WSSV using primers designed from early genes and sequences the Indian isolates for homology analysis. Polymerase chain reaction was performed for the detection confirmation and the PCR products were cloned. Different organs such as gill, head soft tissue, heart tissue, intestine and tail tissue had been used for the PCR assay. Both genes were amplified at the size of 420 bp and 457 bp, respectively. Different duration samples of WSSV post-infection muscle DNAs were analyzed with the two primers and compared with OIE-nested PCR method convincing the early detecting ability of the virus. Sequencing analysis was performed with other isolates from France, China, The Netherlands and Taiwan. Phylogenetic analysis revealed that the Indian isolate was closely related to other isolates.